2018
DOI: 10.1039/c7sc04553k
|View full text |Cite
|
Sign up to set email alerts
|

Ship in a bottle: confinement-promoted self-assembly

Abstract: Lipid vesicles behave like ship-in-a-bottle constructs that direct the ship's assembly following the confinement of key wooden planks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…13 The chain density of the PNIPAm shell depends on the length of PNIPAm blocks and strongly affects the temperature-responsive behavior of the micelles which results in the hysteresis of the cloud point curves. 14 It was also reported that the kinetics of the growth of micellar associates with PNIPAm shells is controlled by structural rearrangement of the associates. 15,16 Recently, a PNIPAm polymer with dodecyl and carboxylic terminal groups (C12-PNIPAm-COOH) was synthesized by RAFT polymerization using S-1-dodecyl-S′-(α,α′-dimethyl-α″acetic acid)trithiocarbonate as a chain transfer agent, and it was shown that it forms micelles in aqueous media with the core formed by the dodecyl terminal groups and having carboxylate terminal groups in the shell periphery.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The chain density of the PNIPAm shell depends on the length of PNIPAm blocks and strongly affects the temperature-responsive behavior of the micelles which results in the hysteresis of the cloud point curves. 14 It was also reported that the kinetics of the growth of micellar associates with PNIPAm shells is controlled by structural rearrangement of the associates. 15,16 Recently, a PNIPAm polymer with dodecyl and carboxylic terminal groups (C12-PNIPAm-COOH) was synthesized by RAFT polymerization using S-1-dodecyl-S′-(α,α′-dimethyl-α″acetic acid)trithiocarbonate as a chain transfer agent, and it was shown that it forms micelles in aqueous media with the core formed by the dodecyl terminal groups and having carboxylate terminal groups in the shell periphery.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The micelles are stabilized kinetically due to a high activation energy barrier which hinders mutual interpenetration of the dense micellar shells of different associates . The chain density of the PNIPAm shell depends on the length of PNIPAm blocks and strongly affects the temperature-responsive behavior of the micelles which results in the hysteresis of the cloud point curves . It was also reported that the kinetics of the growth of micellar associates with PNIPAm shells is controlled by structural rearrangement of the associates. , …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, engineering rules/design principles for generating homogenous supramolecular lipid structures can be proposed herein. It has been known that molecules in confined spaces behave distinctly from that in the bulk ( Yang et al., 2008 ; Lopez-Fontal et al., 2018 ). Thereby, nanoconfinement of lipid molecules is the stellar engineering rule affecting their self-assembly spatially and temporally and thereby determining the structural shape, size, and stability.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Reversible bonds may help to overcome kinetic traps and correct errors during assembly. 2,10,12 Nucleation templates -as in heterogenous nucleation -and geometrical constraints can guide self-assembly and improve yield; 11,30,31 in fact, boundaries aid the self-assembly of lipid vesicles at the molecular scale 32 and of 3D printed particles at the macroscale. 27,29 Multi-component building blocks can form more complex structures than single-component systems and exhibit a wider range of properties; 33,34 furthermore, multi-component systems allow for precise process initiation control.…”
Section: Introductionmentioning
confidence: 99%